Pengaruh Akuntabilitas dan Transparansi Pengelolaan Keuangan Desa terhadap Tingkat Kepercayaan Masyarakat pada Pemerintah Desa: Studi pada Desa Barih Lhok Kecamatan Kuta Cot Glie Kabupaten Aceh Besar - Ulya, Rahmnuna (Jurnal EMT KITA, 2025)
This study aims to analyze the influence of transparency and accountability in village financial management on the level of public trust in Barih Lhok Village, Kuta Cot Glie Subdistrict, Aceh Besar Regency. The research employs a quantitative descriptive approach, collecting data through questionnaires distributed to 85 respondents selected using purposive sampling from the population of Barih Lhok Village. The data obtained were analyzed using multiple linear regression with the assistance of SPSS statistical software. The results indicate that both partially and simultaneously, the variables of transparency and accountability have a significant influence on the level of public trust.
Keywords: Accountability; Transparency; Village Financial Management; Public Trust Level